Réponses

2013-12-13T16:31:33+01:00
A=5a-2a+7a
=10a

b=5x-7+8x+4
=13x-3

c= 3a+5b-7+a-b-3
=4a+4b-10

D=-1+(a+2b+4)+(-a-2b+2)
=-1+a+2b+4-a-2b+2
=5

E=-4ax5ax3a
=60a³

F=(x-3)-(x+5)-(x-7)
=x-3-x-5-x+7
=-x-1

g=3(2z-7)
=6z-21
2013-12-13T16:46:11+01:00
A=5a-2a+7a  = 10 a        
B=5x-7+8x+4  = 13x - 3              
C= 3a+5b-7+a-b-3 = 4 a + 4 b -10 = 4 (a + b - 10/4 ) = 4 ( a + b - 5/2 )
D=-1+(a+2b+4)+(-a-2b+2) =            
E=-4ax5ax3a = - 60 a^3             
F=(x-3)-(x+5)-(x-7) = - x - 1 = - ( x + 1)
G=3(2z-7) = 6 z - 21 = 2 z - 7